1984
DOI: 10.2527/jas1984.5851255x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Measures of Testicular Development and Endocrine Function in Boars

Abstract: SummaryNine blood samples were taken at 30-min intervals from 36 Landrace x Large White boars at each of eight ages (42, 56, 70, 84, 98, 112, 126 and 140 d). Serum concentrations of luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone (T) and estradiol-1713 (E2) were quantified by radioimmunoassay procedures. The maximum concentration of LH and the age at maximum concentration were predicted for each boar. Variability of LH samples was described for each boar by the pooled within age var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…1 and 2 indicated no important differences in circulating concentrations of FSH among boars from TS and C lines. This supports previous work (Schinckel et al 1984) in which boars with larger testes had concentrations of FSH similar to those of boars with smaller testes during sexual maturation. Based on data from the present experiments, there are no differences in feedback regulation of 17b-estradiol on the hypothalamic-pituitary axis in modulation of FSH secretion between boars in the TS and C lines.…”
Section: Discussionsupporting
confidence: 91%
“…1 and 2 indicated no important differences in circulating concentrations of FSH among boars from TS and C lines. This supports previous work (Schinckel et al 1984) in which boars with larger testes had concentrations of FSH similar to those of boars with smaller testes during sexual maturation. Based on data from the present experiments, there are no differences in feedback regulation of 17b-estradiol on the hypothalamic-pituitary axis in modulation of FSH secretion between boars in the TS and C lines.…”
Section: Discussionsupporting
confidence: 91%
“…Although cordycepin can induce the steroidogenic enzyme E2 and testosterone (Hsu et al, 2003;Huang et al, 2004), its effect on FSH has not been reported and awaits future study. Boars with high testes weight had a more rapid increase in E2 concentrations than did boars with low testes weight (Schinckel et al, 1984a(Schinckel et al, , 1984bZanella et al, 1999). The sperm transit through the epididymis takes approximately 10 days in pigs.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, estrogen concentrations in plasma were similar for both groups, which would indicate a similar degree of interstitial cell activity within the testes of treated and control boars (Raeside and Renaud, 1983). Schinckel et al (1984b) found no correlation between average LH and FSH concentrations in boars for blood samples collected from 42 to 140 d of age. However, mean concentrations of both gonadotropins varied in a similar manner over time in boars selected for high or low testicular weight (Schinckel et al, 1984a).…”
Section: Discussionmentioning
confidence: 76%